Debt Policy and Banking Policy - Simons, Henry C. (The Review of Economics and Statistics, 1946)
rrHE scheme of putting our federal debt wholly into two forms, consols and currency,l is obviously too radical for early political consideration. Its virtue is that of indicating a direction for policy which, wisely pursued, would perhaps involve numerous steps and only gradual institutional change. Much can be said for focusing attention upon the radical, ultimate objective, namely, an economy where all private property takes exclusively the forms of government demand obligations (currency or full currency equivalents), government consols (always in process of elimination, save during total war), corporate common stock, and fee interests in real assets (along with an inevitable minimum of business accounts-receivable and